Exercise and Vitamin D Supplementation Modify Spleen Morphology in Lean, but not, in Monosodium-Glutamate-Obese Rats - Maria Guareschi Zoé; Marieli Ceglarek Vanessa; Fontes Rodrigues Patrick; Pierre Huning Luiz; Festinalli Cintia; Paulo de Arruda Amorim João; Grassiolli Sabrina (Journal of Spleen And Liver Research, 2019)
An experimental study examines how exercise and vitamin D supplementation affect spleen morphology in lean versus MSG‑obese rats, discussing immunologic implications.
Keywords: Swimming